Paving the Way for Prosperous Cities and Territories : Urbanization and Territorial Review of the Dominican Republic - World Bank (Washington, DC : World Bank, 2022)
Over the past four decades and prior to the pandemic, the Dominican Republic (DR) experienced high economic growth rates, which were accompanied by an expansion of the middle class and a significant reduction of poverty rate. During the same period, the country became predominantly urban, and its territories evolved from rural and agricultural spaces to large metropolitan areas, consolidating tourism poles in coastal areas and suburban spaces where manufacturing emerged, fueled by the creation of Special Economic Zones (SEZ). In 2020, it is estimated that 82.5 percent of the Dominican Republic’s population lives in urban areas; and by 2050 this number will go up to 92 percent.While the economic and territorial transformation of the country has generated opportunities for its population, it has also created a number of challenges which require to be tackled. Such as providing quality basic services, assuring safe and affordable housing solutions to the fast-growing population, assuring firms count with the right enabling environment in the places where they locate and, more recently, supporting the Coronavirus (COVID-19) recovery efforts to build a better future for the country. The government of the Dominican Republic has recognized the opportunities that come with better leveraging its territory and tackling current development challenges; and is pushing to advance an ambitious territorial development reform. This DR’s Urbanization and territorial development review aims to inform and contribute to the Government’s effort by (i) providing evidence of the main territorial challenges currently being faced by the country with a specific focus on urban areas and lagging regions; (ii) review the current (and proposed reforms to the) regulatory framework for territorial planning and local government finance; and (iii) inform policy decisions at the national, regional, and local levels for ways ahead to address the territories challenges and embrace its opportunities, and to implement the proposed reforms.